Additive Manufacturing Technologies: An Overview about 3D Printing Methods and Future Prospects - Espinosa, María del Mar; Domínguez, Iris A.; Romero, L.; Jiménez, Mariano; Domínguez, Manuel (Complexity (New York, N.Y.), 2019)
The use of conventional manufacturing methods is mainly limited by the size of the production run and the geometrical complexity of the component, and as a result we are occasionally forced to use processes and tools that increase the final cost of the element being produced. Additive manufacturing techniques provide major competitive advantages due to the fact that they adapt to the geometrical complexity and customised design of the part to be manufactured. The following may also be achieved according to field of application: lighter weight products, multimaterial products, ergonomic products, efficient short production runs, fewer assembly errors and, therefore, lower associated costs, lower tool investment costs, a combination of different manufacturing processes, an optimised use of materials, and a more sustainable manufacturing process. Additive manufacturing is seen as being one of the major revolutionary industrial processes of the next few years. Additive manufacturing has several alternatives ranging from simple RepRap machines to complex fused metal deposition systems. This paper will expand upon the structural design of the machines, their history, classification, the alternatives existing today, materials used and their characteristics, the technology limitations, and also the prospects that are opening up for different technologies both in the professional field of innovation and the academic field of research. It is important to say that the choice of technology is directly dependent on the particular application being planned: first the application and then the technology.